2018
DOI: 10.48550/arxiv.1803.06632
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Guided FP-growth algorithm for multitude-targeted mining of big data

Lior Shabtay,
Rami Yaari,
Itai Dattner

Abstract: In this paper we present the GFP-growth (Guided FP-growth) algorithm, a novel method for multitude-targeted mining: finding the count of a given large list of itemsets in large data. The GFP-growth algorithm is designed to focus on the specific multitude itemsets of interest and optimizes the time and memory costs. We prove that the GFPgrowth algorithm yields the exact frequency-counts for the required itemsets. We show that for a number of different problems, a solution can be devised which takes advantage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Their designed structures can be updated incrementally with new transactions. Shabty et al [14] designed a novel method called Guided FP-growth (GFP-growth) for multitude-targeted mining. The fast and generic tool GFP-growth can determine the frequency of a given large list of itemsets, which serve as the targets, in a large dataset from an FP-tree [45] based on Target Itemset Tree.…”
Section: Target-oriented Queryingmentioning
confidence: 99%
See 1 more Smart Citation
“…Their designed structures can be updated incrementally with new transactions. Shabty et al [14] designed a novel method called Guided FP-growth (GFP-growth) for multitude-targeted mining. The fast and generic tool GFP-growth can determine the frequency of a given large list of itemsets, which serve as the targets, in a large dataset from an FP-tree [45] based on Target Itemset Tree.…”
Section: Target-oriented Queryingmentioning
confidence: 99%
“…To satisfy the requirements of users, a series of frequency-based methods that can search for specific goal items were proposed. Till now, target-oriented frequent itemset querying [14], association rule querying [15], [16], [17], and sequential pattern querying (SPQ) [18], [19], [20] have performed significant roles in querying in the database. The three target-oriented technologies can efficiently excavate patterns and rules involving a subset of certain items, such as targeted queries, and have shown significant potential in several real-life situations [21].…”
Section: Introductionmentioning
confidence: 99%
“…The experiments demonstrated that the new data structure is up to 43% smaller than IT on average in terms of memory consumption. As an FP-tree-based algorithm, guided FP-growth (GFP-growth) [18] was proposed. It can determine the support of a given large list of itemsets (that are regarded as targets) using the target itemset tree.…”
Section: Target Pattern Queryingmentioning
confidence: 99%
“…Researchers have defined this interesting task as target-oriented pattern mining [17]. To date, several studies have been conducted on target-based pattern mining, such as target-oriented frequent itemset querying [18], target-based association rule mining [19], [20], and targeted sequential pattern querying [21]- [23]. As stated previously, customers are usually not interested in receiving all discount messages according to the recommender system.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, mining user-specified itemsets was proposed as a new interesting task, named targeted utility mining (abbreviated as TaUM) [29], [30]. To our best knowledge, there are some studies about targetbased pattern mining such as target-oriented frequent itemset querying [31], target-based association rule mining [32], [33] and sequential pattern querying [34]- [36]. However, there is little information in the literature about TaUM.…”
Section: Introductionmentioning
confidence: 99%